Towards sustainable coffee production in Vietnam: addressing irrigation issues. Vietnam Project - Amarasinghe, Upali A.; Hoanh, Chu Thai; D'Haeze, Dave; Hung, T.Q. (2013)
Inefficient use of groundwater perils Vietnamﾒs coffee production, the second largest of the world after Brazil. Unsustainable coffee production in Vietnam has both national and global ramifications. Nationally, it is so crucial that coffee is the second largest export-earning crop after rice, and the production supports livelihoods of significant rural agricultural population with small land holdings. Internationally, Vietnamﾒs coffee exports meet the rapidly growing demand, and account 19% of worldﾒs coffee exports in 2010, up from only 2% in 1990. This paper examines groundwater irrigation issues that constraint sustainable coffee production in Vietnam. January to April is a crucial period of coffee crop growth: it requires irrigation, because rainfall meets only 25% of the potential crop-evapotranspiration demand. According to crop phenology, this period also requires induced water stress, because it coincides with breaking the dormancy of coffee buds and initiation of cherry development, which is crucial for higher yield. The paper recommends irrigation supply of 120 to 150 mm/ha between January and April in a year preceded by good or average rainfall respectively in November and December. This is equivalent to 456 liters/plant/round in 3 rounds/year, which is a significant reduction from the recommend level of 650 liters/plant/round. Synchronizing this irrigation supply with other inputs could increase average yield up to 4,000 kg/ha, from the present level of 2,400 kg/ha. These require experimental studies to understand the timings of irrigation rounds and other inputs, capacity building of farmers to follow the irrigation and input application schedules, and public awareness campaigns to raise the importance of improved irrigation management methods.